Injustice Management of Adat Land: Learn from Maranfenfen in Aru - Selvone Christin Pattiserlihun; Mustaqim Pabbajah; Ratri Nurina Widyanti (DIALEKTIKA, 2023)
The issue of Adat (customary) land management carried out by the government as a ruler of indigenous peoples in the world is not a new thing to be discussed. Many phenomena of Adat land management deviate from human rights. This problem occurs because indigenous peoples still lack knowledge about laws and rights to Adat land. The State has strong control to regulate and take rights over all forms of natural wealth in Indonesia, including land because it is stated in the UUD NKRI 1945, Article 33 point 3 "earth and water and the natural resources contained therein are controlled by the state and used for the greatest prosperity of the people."Â This paper aims to discuss injustice in Adat land management as the rights of the indigenous peoples in Marafenfen, Aru Islands, Maluku province, which the government seized through one of the government agencies in the field of national defense (TNI-AL). This issue proves that the rights of indigenous peoples to Adat lands are still unfair, especially in Indonesia.